ATB MobileApplication dalam Pelayanan Air Bersih di PT Adhya Tirta Batam: Indonesia - Karol Teovani Lodan (Prodi Ilmu Administrasi Negara, 2018)
Adhya Tirta Batam (ATB) is entrusted as clean water provider in Batam Island based on 25 Year concession of Batam Industrial Development Authority (now BP Batam). The purpose of this research is to analyze ATB mobile application in providing clean water service in Batam City. This research is a descriptive with qualitative approach. The focus of this research is the application of ATB mobile viewed from publications, interactions and transactions point of views. The results show this android-based mobile applications which can be downloaded from the Google Play Store by customers can be used as a mean to obtain information: payment locations, loggers, complaints, water usage charts, bill info, and information. The reason behind the availability of 6 (six) features because the information is the most basic or essential needed by the community. There is only one feature which gives a brief description of its usefulness, it is the feature information. Practically, this application is not so difficult to use and can be accessed anytime and anywhere as long as connected to the internet network. Viewing from the main classes of e-government, this application is equipped with a class of publications, they are feature information, payment locations, loggers, water usage graphics and bill info and interaction which is in complaint features. Relating to the the transfer of money from one party to another in transactions feature, shall be be equipped with a good security system so that the customers are comfortable and safe to make any transfer. Yet currently ATB Mobile Application has not provided such activity because it has not been equipped with a transaction tool which can guarantee the security of customers in the transaction.